Bacterial biofilms in patients with chronic rhinosinusitis - Dworniczek, E; Fraczek, M; Seniuk, A; Kassner, J; Sobieszczańska, B; Adamski, J; Ciesielska, U (Folia microbiologica, 2009)
The possible presence of biofilms was examined in mucosal specimens of 15 patients, undergoing functional endoscopic sinus surgery or a modified Caldwell-Luc approach for chronic rhinosinusitis (CRS). Biofilms were found in 7 of the 15 patients, positive cultures being obtained in most samples, which supports the role of biofilms as an important factor in the pathogenesis of CRS.
Keywords: sinusitida; endoskopie; Humans; lidé středního věku; Chronic Disease; Female; mladý dospělý; dospělí; nosní sliznice; Microscopy, Electron, Scanning; lidé; Endoscopy; Nasal Mucosa; rýma; Adult; ženské pohlaví; Male; biofilmy; Middle Aged; chronická nemoc; mikroskopie elektronová rastrovací; Adolescent; Young Adult; Sinusitis; mužské pohlaví; Rhinitis; mladiství; Biofilms